A Room‐Temperature Processable PDI‐Based Electron‐Transporting Layer for Enhanced Performance in PDI‐Based Non‐Fullerene Solar Cells. Issue 18 (5th August 2016) - Yu, Jiangsheng; Xi, Yuyin; Chueh, Chu‐Chen; Zhao, Dongbing; Lin, Francis; Pozzo, Lilo D.; Tang, Weihua; Jen, Alex K.‐Y.
Abstract : In this study, it is demonstrated that a facile room‐temperature processed amine functionalized perylene‐diimide (PDIN) can function as an efficient electron‐transporting layer (ETL) to enhance the photovoltaic performance of inverted PDI‐based non‐fullerene solar cells. It is showed that the PDIN ETL possesses respectable mobilities and interfacial doping capability to the PDI‐based acceptors to facilitate the charge transport and extraction in the devices. Moreover, it can modulate the morphological evolution of the bulk‐heterojunction (BHJ) atop to result in a more crystalline, face‐on orientation because of its improved compatibility to PDI‐based acceptors. Consequently, the PDIN ETL enables the derived devices to have 10% higher power conversion efficiency (PCE) than the reference device. In addition, the PDIN can also be used as a surface modifier on ZnO to result in a ≈14% enhanced PCE than that of the pristine ZnO‐based device. This study shows the feasibility of modulating the BHJ of non‐fullerene organic photovoltaics by rationally selected ETLs to facilitate exciton dissociation and collection of the devices. Abstract : A room‐temperature processable organic perylene‐diimide‐based electron‐transporting layer (ETL) is demonstrated to enhance the performance of inverted PDI‐based organic solar cells. The amine functionalized perylene‐diimide ETL can effectively modulate bulk‐heterojunction morphology atop to induce improved out‐of‐plane π–π stacking and associated lamellar orientation. Consequently, it can replace or modify the regularly used ZnO ETL for enhanced photovoltaic performance.